KULINTANGAN: A STUDY OF PRODUCTION PROCESS - Adsone Matthew Mitty Gabu, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The main purpose of this study is to document the production process of the Kulintangan. Data collection was conducted through interviews and observations. The Kulintangan, an idiophone categorized musical instrument is a set of small kettle gongs positioned straight in a single row on two cords in a small wooden frame. There is no traditional system to notate the Kulintangan as music is passed down by tradition from generation to generation. Distinctions are found in different combinations of instruments, varying dance, tempos, tunings and production process. While other musical instruments in Sabah are made from natural material, the Kulintangan is made from either zinc or bronze. The process of producing Kulintangan is a highly skilled process, handed down through generation. Five tools are used to produce a set of Kulintangan. There are 6 processes in the production of the Kulintangan, from the selection of raw material to the final product. Documenting the production process provides documented information and demonstration of the Kulintangan. Thus, revive and continues intangible cultural heritage for the future.